Does the use of IV tPA in the current era of rapid and predictable recanalization by mechanical embolectomy represent good value?. (12th January 2016) - Chandra, Ronil V; Leslie-Mazwi, Thabele M; Mehta, Brijesh P; Derdeyn, Colin P; Demchuk, Andrew M; Menon, Bijoy K; Goyal, Mayank; González, R Gilberto; Hirsch, Joshua A
Abstract : As healthcare delivery in the USA transforms into a model that at its core requires value-based considerations, ischemic stroke is confronted by intersecting forces. Modern techniques allow rapid revascularization in the majority of patients with large vessel occlusions. Dramatic advances in the evidentiary basis for mechanical embolectomy are increasing the number of patients treated with this therapy. A key part of the therapeutic arsenal in many patients treated with interventional techniques has been concurrent intravenous thrombolysis. We consider whether this paradigm warrants change.